Pengaruh Literasi Keuangan, Pengendalian Diri, dan Status Sosial Ekonomi Orang Tua Terhadap Perilaku Konsumtif mahasiswa Universitas YPPI Rembang : Literasi Keuangan, Pengendalian diri, Status Sosial Ekonomi Orang Tua, Perilaku Konsumtif - Moriska Hesti Ningsih; Damayanti (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to demonstrate the influence of financial literacy, self-control, and parental socioeconomic status on the consumer behavior of students at the Faculty of Economics and Business, YPPI University, Rembang. The population used in this study were students at the Faculty of Economics and Business, YPPI University, Rembang, from the 2022-2024 intake. The sampling technique used in this study was proportional stratified random sampling. Respondents selected for this study were students in their third, fifth, and seventh semesters. The data analysis technique used was SPSS. Data analysis was performed using a multivariate linear regression model. The results of this study indicate that financial literacy and self-control have a positive and significant effect on student consumer behavior. However, parental socioeconomic status has a positive but insignificant effect on student consumer behavior at YPPI University, Rembang. This research model only explains 64.3% of the total parental socioeconomic status, thus indicating that 35.7% remains unexplained or is caused by external factors. Keywords: Financial Literacy, Self-Control, Parents' Socioeconomic Status, Consumptive Behavior